2017
DOI: 10.3389/fphys.2017.00596
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis for Glycopatterns and Complex-Type N-Glycans of Glycoprotein in Sera from Chronic Hepatitis B- and C-Infected Patients

Abstract: Background: Chronic infection with HBV (CHB) or HCV (CHC) is the most common chronic viral hepatitis that can lead to cirrhosis and hepatocellular carcinoma in humans, their infections have distinct pathogenic processes, however, little is known about the difference of glycoprotein glycopatterns in serum between hepatitis B virus (HBV)- and hepatitis C virus (HCV)-infected patients.Methods: A method combining the lectin microarrays, letin-mediated affinity capture glycoproteins, and MALDI-TOF/TOF-MS was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The N-glycans were released by PNGase F glycosidase (New England Biolabs, Beverly, MA) according to previous protocols (25, 26). Briefly, 200 μg of isolated glycoproteins were concentrated and desalted by adding to a size-exclusion spin ultrafiltration (Amicon Ultra-0.5 mL 10,000 MW cut off, Millipore).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-glycans were released by PNGase F glycosidase (New England Biolabs, Beverly, MA) according to previous protocols (25, 26). Briefly, 200 μg of isolated glycoproteins were concentrated and desalted by adding to a size-exclusion spin ultrafiltration (Amicon Ultra-0.5 mL 10,000 MW cut off, Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…The MAL-I-enriched N-linked glycans were characterized using MALDI-TOF/TOF-MS (UltrafleXtreme, Bruker Daltonics, Germany) as previously described (25, 26). Briefly, the glycans were resuspended in 10 μL of methanol, then glycan samples and DHB were spotted on a MTP AnchorChip, respectively to recrystallize the glycans.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was then used in the lectin microarrays. Finally, incubation was performed in the chamber at 37 °C for 3 h [9].…”
Section: Saliva and Serum Lectin Microarraysmentioning
confidence: 99%
“…The membrane was incubated with Cy5-labeled (GE Healthcare, Buckinghamshire, UK) lectins (2 mg/) at 4 °C overnight in the dark. Finally, the membrane was scanned using a phosphorimager (Molecular Dynamics Inc., Sunnyvale, CA, USA) [9].…”
Section: Lectin Blot Analysismentioning
confidence: 99%
“…N-glycans profiles by MALDI-TOF/TOF-MS have shown that glycans F1N5H4 (bisecting), N5H5 (bisecting) and F1N6H3F1 are overexpressed in CHB patients. In contrast, glycans F1N5H4 (bisecting), N3H5, N6H5 and F1N5H6 are overexpressed in CHC patients, compared to healthy individuals [194]. The over-expression of bisecting glycan F1N5H4 was also observed in liver cancer.…”
Section: Glycans As Potential Biomarkers In Other Diseasesmentioning
confidence: 99%